Implementasi Kebijakan Standar Pelayanan Syahbandar (Studi tentang Eksepsi Penumpang sesuai Permenhub Nomor 37 Tahun 2015 di Pelabuhan Pantai Baru Kabupaten Rote Ndao) - Amin, Usman Lauda; Atang, Ahmad; Laan, Rahmad; Beni, Wahid Hasyim TRA; Darajad, Syarifuddin (Universitas Hamzanwadi, 2026)
This study aims to describe and analyze the implementation of passenger service standards by the Harbormaster based on the Regulation of the Minister of Transportation Number 37 of 2015 at Pantai Baru Port, Rote Ndao Regency, as well as to examine passengers’ perceptions of the services provided. This research employs a qualitative approach with data collection methods including observation, in-depth interviews, and documentation. Research informants were purposively selected and consisted of Harbormaster officials, port officers, security personnel, the Rote Ndao Regency Transportation Office, and sea transportation passengers. Data analysis was conducted using a descriptive qualitative method through the stages of data reduction, data presentation, and conclusion drawing, with triangulation techniques applied to ensure data validity. The results indicate that the implementation of Harbormaster service standards at Pantai Baru Port has been carried out in accordance with regulatory provisions, particularly in terms of maritime safety and security. However, the implementation of these service standards has not yet been fully optimal, especially regarding facility comfort, queue management, departure punctuality, and transparency of service information. Passengers generally perceive the Harbormaster’s services as fairly good in terms of safety and the friendliness of officers, but they continue to highlight the limited port facilities and the weak information system as the main sources of dissatisfaction. This study concludes that there is a gap between normative service standards and actual service practices in the field, indicating the need for improvements in facilities, strengthening of human resources, and enhancement of communication and service information systems to improve the quality of public services at ports in archipelagic regions.